Aggregation and construction mechanisms of microbial extracellular polymeric substances with the presence of different multivalent cations: Molecular dynamic simulation and experimental verification. (1st April 2023) - Peng, Sainan; Wang, Zhiyue; Yu, Pingfeng; Liao, Guiying; Liu, Rui; Wang, Dongsheng; Zhang, Weijun
Highlights: A molecular model was built to reveal the arrangements and dynamic characteristics of biopolymers in EPS. Biopolymers form agglomerates spontaneously through electrostatic and hydrophobic interactions. Rearrangement of EPS molecular conformation reduced the exposure of hydrophilic groups. Contact of biopolymers promoted by multivalent cations enhancing the intermolecular forces and compactness of EPS. The hydration of Al 3+ and Mg 2+ affect the stability of association with biopolymers. Abstract: Interactions between cations and extracellular polymeric substances (EPS) play an important role in the formation of microbial aggregates and have key effects on the physical properties of activated sludge across wastewater and sludge treatment process. Here, a molecular model of EPS cluster in activated sludge was constructed and simulated by molecular dynamics (MD) to probe the structural properties of EPS and the interaction between EPS and prevalent multivalent cations (Ca 2+, Mg 2+, Al 3+ ). Then the predicted changes in physical properties were validated against the dynamic light scattering, XAD resin fractionation and rheology test. The binding dynamics and interactions mechanisms between multivalent cations and EPS functional groups were further investigated using MD in combination with spectroscopic analysis. Results suggest that biopolymers are originally aggregated by electrostatic and intermolecular interactions forming dynamic clusters with negatively charged surface functional groups, which induced electrostatic repulsion preventing further agglomeration of biopolymer clusters. In the presence of multivalent cations, surface polar functional groups in biopolymers are connected, causing the rearrangement of EPS molecular conformation that forms larger and denser agglomerates. Reduced solvent accessible surface area, enhanced hydrophobicity, and increased binding free energy lead to a strong gel-like network of EPS. Ca 2+ and Al 3+ predominantly interact with functional groups in polysaccharides, promoting agglomeration of macromolecules. In contrast, Mg 2+ and Al 3+ disrupted the secondary structure of proteins, exposing hydrophobic interaction sites. Al 3+ can better agglomerate biopolymers with its higher positive charge and shorter coordination distance as compared to Ca 2+ and Mg 2+, but compromised by the effect of hydration. This work offers a novel approach to explore the construction and molecular aggregation of EPS, enriching the theoretical basis for optimization of wastewater and sludge treatment. Graphical abstract: Image, graphical abstract